Securitization of the Corona Virus and Adopting State Restrictive Measures in the Fight against the viral Pandemic (Case Study of the United Kingdom, Germany, and Australia) - Nima Rezaei; Saeed Mirtorabi (دولت‌پژوهی, 2020)
Various governments around the world have put tough restrictive measures on the agenda to combat the outbreak of the Covid-19 virus. Actions that are unbearable for people under normal circumstances. These restrictive measures and extraordinary means have so far been accepted by the public (despite popular protests in some countries). This study seeks to answer the main question: "Which of theories can best explain or understand the restrictive actions of different states in the face of coronavirus?" It hypothesizes that "use extraordinary means such as the closure of universities, mosques, religious shrines, discos and nightclubs, etc. "Different governments use them in the face of the coronavirus, due to the “securitization' of public health from the risk of a viral pandemic by different governments." The theory of "securitization" is therefore used, because in "securitization", the a securitising actor defines a security issue as a threat to the survival of a referent object which is claimed to has a right to survive. Since a question of survival necessarily involves a point of no return at which it will be too late to act, it is not defensible to leave this issue to normal politics. The securitising actor therefore claims a right to use extraordinary means or break normal rules, for reasons of security; Tools that are normally unjustifiable and not tolerated. At the same time, the actions of a transnational actor such as the World Health Organization(WHO) in "securitization" the coronavirus are examined using the concept of " Macrosecuritization ".